Comparative Plastid Genomics of Green-Colored Dinoflagellates Unveils Parallel Genome Compaction and RNA Editing - Matsuo, Eriko; Morita, Kounosuke; Nakayama, Takuro; Yazaki, Euki; Sarai, Chihiro; Takahashi, Kazuya; Iwataki, Mitsunori; Inagaki, Yuji (Frontiers in Plant Science, 2022)
Dinoflagellates possess plastids that are diverse in both pigmentation and evolutionary background. One of the plastid types found in dinoflagellates is pigmented with chlorophylls a and b (Chl a+b) and originated from the endosymbionts belonging to a small group of green algae, Pedinophyceae. The Chl a+b-containing plastids have been found in three distantly related dinoflagellates Lepidodinium spp., strain MGD, and strain TGD, and were proposed to be derived from separate partnerships between a dinoflagellate (host) and a pedinophycean green alga (endosymbiont). Prior to this study, a plastid genome sequence was only available for L. chlorophorum, which was reported to bear the features that were not found in that of the pedinophycean green alga Pedinomonas minor, a putative close relative of the endosymbiont that gave rise to the current Chl a+b-containing plastid. In this study, we sequenced the plastid genomes of strains MGD and TGD to compare with those of L. chlorophorum as well as pedinophycean green algae. The mapping of the RNA-seq reads on the corresponding plastid genome identified RNA editing on plastid gene transcripts in the three dinoflagellates. Further, the comparative plastid genomics revealed that the plastid genomes of the three dinoflagellates achieved several features, which are not found in or much less obvious than the pedinophycean plastid genomes determined to date, in parallel.